The evolution of the role of the headteacher in Greek secondary schools from the beginnings of the modern Greek state to the present, with emphasis on recent years. - Panagiotis K Bairaktaris (2002)
Educational management is an underdeveloped field in Greece. Although there has been some effort made in the area of educational management in general, there have been no attempts at the study of school management. One possibly fruitful approach to the subject is the study of the role of headteachers within schools. This could aid in explaining many aspects of the situation in which Greek schools find themselves today, and also in introducing improvements into the secondary educational system. It is important to observe exactly how far and in what ways the historical evolution of Greek education has defined the roles of headteachers. An attempt at studying the roles of heads within the framework of Public Administration, the Administration of Education and, more precisely, the administration of secondary education, should give a full picture of the situation existing within the secondary school administrative system.As for the differences in style and practice which have become discernible in recent years, these lead us to specific conclusions concerning the recent situation in secondary education in Greece. An additional study of the present day situation of Heads, such as the payment of heads, female headteachers etc., gives a more complete view of the roles of Heads and better describes how those roles have evolved. This field of study leads towards conclusions concerning improvements for the secondary school administrative system and introduces measures, which could be of use in the advancement of Greek secondary schools.